w-(-3)=7
Pretend that there is a -1 in front of the bracket
w-1(-3)=7
Mutiply the bracket by -1
(-1)(-3)=3
w+3=7
Move +3 to the other side. Sign changes from +3 to -3.
w+3-3=7-3
w=4
Answer: w=4
16.445 I have no expectation sorry.
Answer:
a c
Step-by-step explanation:
<em>So</em><em> </em><em>the</em><em> </em><em>right</em><em> </em><em>answer</em><em> </em><em>is</em><em> </em><em>of</em><em> </em><em>option</em><em> </em><em>C</em>
<em>Look</em><em> </em><em>at</em><em> </em><em>the</em><em> </em><em>attached</em><em> </em><em>picture</em>
<em>Hope </em><em> </em><em>it</em><em> </em><em>will</em><em> </em><em>help</em><em> </em><em>u</em><em> </em><em>.</em><em>.</em>